Evaluation of the International Labor Organization’s Reports on Turkey in Terms of ILO’s Audit Activity - İzzettin As; Abdullah Önal (Sosyal Siyaset Konferansları Dergisi)
One major objective of the International Labor Organization (ILO) is to establish social balance through the establishment of improved working conditions, to influence the economic process which is the subject of international competition, and to eliminate the drawbacks of this process. In fulfilling this objective, the ILO uses its audit function as an important tool. The audit function enables the ILO to consider whether its established norms are implemented by its member states. It also allows the ILO to monitor the implementation of the social provisions contained in the ILO Conventions. Audit, which constitutes an important dimension of the ILO’s rulemaking activity, is carried out in two ways: regular auditing and complaint-based auditing. Since 1932, when Turkey became a member of the ILO, Turkey has been an addressee of this audit activity. Turkey has been frequently placed on the ILO’s agenda in the sessions held within the scope of regular auditing as well as complaint-based auditing. In the meetings where Turkey has been discussed and in the reports prepared on Turkey, the harmonization of national legislation and ILO norms and the problems affecting implementation have been the main issues for evaluation. The regular and complaint-based audit conducted by the ILO have been very effective in Turkey as they have helped in improving the country’s effort to make legislative arrangements to improve working conditions for their residents. Against this background, this study will consider Turkey’s implementation of ILO norms and analyze how Turkey is handled within the scope of the ILO’s audit activities. A brief discussion on the changes that have occured in Turkey as a result of the indirect or direct effects of the ILO’s audit activities will also be presented. Within this framework, the relationship between the ILO and Turkey and the effects of this relationship on Turkish labor legislation will be considered.